A major dengue epidemic in 2022 in Nepal: need of an efficient early-warning system - Dhoubhadel, Bhim Gopal; Hayashi, Yumiko; Domai, Fleurette Mbuyakala; Bhattarai, Suraj; Ariyoshi, Koya; Pandey, Basu Dev (Frontiers in Tropical Diseases, 2023)
Dengue has become a recurrent and growing threat to public health in Nepal. The epidemic in 2022 was the largest ever reported, with cases being reported in all of the country’s seven provinces and 77 districts. Despite the establishment of an early-warning and reporting system (EWARS) in 1997, the lack of clear criteria for alarm signals and outbreak definitions in national guidelines delayed the epidemic declaration in 2022, which resulted in an increased number of cases and fatalities. For this article, we analyzed national data from previous years, which demonstrate that an epidemic could have been declared early in July, and that that would have resulted in fewer cases and fatalities if clear criteria for outbreak declarations had also been put in place. We also reviewed the existing national guidelines for dengue prevention and control, and propose recommendations to improve their implementation, particularly with regard to vector control measures. This article also highlights the need for a coordinated effort between multisector stakeholders, strengthened disease surveillance systems, and the establishment of predefined alarm signals and epidemic declaration criteria so that future epidemics are identified in a timely manner. The early outbreak warning system can potentially prevent future large outbreaks and minimize their negative impacts on the country’s health systems and economy.